(untitled) (Interdisciplinary Studies Journal, 2024)
Fashion is an interdisciplinary area of study that addresses social, historical, environmental, gender, health issues, among others, having a strong relationship with the ways of dressing an individual or society. This study aims to investigate how the use of clothing affects the health of subjects. For this purpose, a scoping review was carried out, with a qualitative and exploratory, approach in the literature from 2017 to 2023, through the PubMed and Periódicos Capes databases. Content analysis was used to present significant results on the subject. Six crucial issues in this relationship were identified: environmental pollution, dermal contamination, bodily, anthropometric and thermophysiological issues, pressure exerted by the product, safety and standards, and aging issues. It was observed that clothing influences both emotional aspects and quality of life and well-being, addressing practical aspects of adornment, protection and modesty. However, there is a clear need for deeper research and practical measures to meet users’ needs and promote health. This study aims to contribute to research in fashion and health-related areas, drawing attention to the topic and opening up possibilities for future research.